Distribution of the heavy metals Co, Cu, and Pb in sediments and Typha spp. And Phragmites mauritianus in three Zambian wetlands. (15th February 2022) - Nabuyanda, Misery Mulele; Kelderman, Peter; van Bruggen, Johan; Irvine, Kenneth
Abstract: Zambia has been mining cobalt (Co), copper (Cu), and lead (Pb) for over a century, with discharges entering wetlands without investigations on the level of sediment pollution and how to solve it. This present study investigated: 1) the extent to which Co, Cu, and Pb that enter through mining wastewater were distributed in the sediment of three wetlands (Uchi, Mufulira, and Kabwe) in Zambia and 2) the accumulation and distribution of the heavy metals in two emergent wetland plants, Phragmites mauritianus, and Typha spp. in order to evaluate their potential for phytoremediation of metals. Samples from three sections (inlet, middle section and outlet) of each wetland were analyzed for the heavy metal contents. Sediment contents of Co and Cu were significantly higher in the Uchi wetland than in the other two, while Pb was significantly higher in the Kabwe wetland. Cu in all the wetlands were found to be at levels considered a threat to aquatic life, with Pb contents in Kabwe a risk to human health. Both P. mauritianus and Typha spp acted as excluder species for Co, Cu, and Pb, showing bioaccumulation factor (BAF) < 1 and Translocation factor (TF) < 1 for all wetlands. As neither species accumulated cellularly toxic concentrations of Co, Cu, and Pb, they could grow in the contaminated sediments. Currently, methods used to solve historic mining impacts in Zambian wetlands aim at improving water flow and reducing flooding without attending to the heavy metal contents of the sediments. From this study, P. mauritianus and Typha spp. provide the potential for phytostabilisation to settle and contain polluted sediments. Graphical abstract: Image 1 Highlights: The research involved assessment of heavy metals in sediments and P. mauritianus and Typha spp. The study determined the bioaccumulation and translocation factors from sediments to plant parts and from roots to shoots, respectively. The study determined the phytoremediation possibility of the two study plant species. The two species survived heavy metal polluted sediments that would otherwise be considered toxic to plants. The study plant species were found to be excluder species useful for phytostabilisation not phytoextraction.